Effect of reduced graphene oxide on thermal property of recycled textile polyamide - Petterson Borges Machado; Marisa Cristina Guimarães Rocha; Mônica Calixto de Andrade; Fernando Loureiro Stavale Junior; Suzana Bottega Peripolli; José Brant de Campos (Journal of Materials Research and Technology, 2024)
This study explored the impact of reduced graphene oxide (rGO) addition on the thermal properties of recycled polyamide (PARec) obtained from repurposed textile industry microfibers initially earmarked for landfill disposal. Characterization of PARec involved techniques like differential scanning calorimetry (DSC), thermogravimetric analysis (TG), Fourier-transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). RGO was characterized through Raman spectroscopy, scanning electron microscopy (SEM), and X-ray diffraction (XRD). Mixtures with varying rGO concentrations, such as PARec-1 (0.1% rGO), PARec-5 (0.5% rGO), and PARec-10 (1% rGO), were prepared and processed in a twin-screw extruder. SEM images at PARec show good dispersion of rGO in the polymer matrix. Thermal properties were determined via DSC and TG, revealing the presence of polyamide 6 in PARec-0 and indicating rGO's quality. Notably, PARec-10 exhibited a slight 3.8% increase in melting temperature and a 7.5% rise in crystallization temperature. These results suggest the potential for improved thermal properties with rGO incorporation. The study contributes to understanding polymer blend thermal properties and introduces an innovative, efficient polymer waste recycling method aligned with sustainability principles.